2009
DOI: 10.1182/blood-2008-05-160200
|View full text |Cite
|
Sign up to set email alerts
|

High-dose therapy followed by autologous purged stem cell transplantation and doxorubicin-based chemotherapy in patients with advanced follicular lymphoma: a randomized multicenter study by the GOELAMS with final results after a median follow-up of 9 years

Abstract: Autologous stem cell transplantation (ASCT) as first-line therapy for follicular lymphoma (FL) remains controversial. The multicenter study randomized 172 patients with untreated FL for either immunochemotherapy or high-dose therapy (HDT) followed by purged ASCT. Conditioning was performed with total body irradiation (TBI) and cyclophosphamide. The 9-year overall survival (OS) was similar in the HDT and conventional chemotherapy groups (76% and 80%, respectively). The 9-year progression-free survival (PFS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
93
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 41 publications
4
93
1
3
Order By: Relevance
“…On the one hand, it raises the possibility that a better control of the disease could postpone the use of therapy (such as mitoxantrone, fludarabine or autologous stem cell transplant conditioning regimen) at risk of secondary myeloid disorder in the relapse setting, but on the other hand, it could also be associated to the reduced course of cytotoxic therapy in the rituximab arm. 17,25,26 Nonetheless, it must be noted that no overall difference in the incidence of secondary malignancies was observed between the two arms of treatment. Even though progressive multifocal leukoencephalopathy is exceptional, its association with the use of rituximab is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it raises the possibility that a better control of the disease could postpone the use of therapy (such as mitoxantrone, fludarabine or autologous stem cell transplant conditioning regimen) at risk of secondary myeloid disorder in the relapse setting, but on the other hand, it could also be associated to the reduced course of cytotoxic therapy in the rituximab arm. 17,25,26 Nonetheless, it must be noted that no overall difference in the incidence of secondary malignancies was observed between the two arms of treatment. Even though progressive multifocal leukoencephalopathy is exceptional, its association with the use of rituximab is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published 10-year update of the GOELAMS 064 trial showed a plateau phase on the progression-free survival curve for transplanted patients which might suggest that HDC-ASCT could potentially cure some FL patients. 18 The reason for the absence of proven OS benefit is still unclear and may be related to the use of HDC-ASCT as salvage therapy for those patients who did not receive transplantation up front, or to long-term toxicities, including secondary malignancies occurring after HDC-ASCT. However, secondary malignancies have also been reported in non-transplanted patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have only included patients undergoing transplantation beyond first response, as this is the currently accepted indication for transplantation in FL. [18][19][20] A prospective study comparing auto-SCT with RIST in this setting unfortunately failed due to poor accrual, 16 and further prospective comparative studies in this setting are unlikely to be performed. Therefore, retrospective studies describing these two forms of transplant provide an important source of data.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] By contrast, auto-SCT is associated with a low early NRM of o5%. 2,3,[18][19][20] Late toxicities must also be taken into consideration when selecting a transplant strategy. Thus following an auto-SCT the development of secondary MDS (myelodysplastic syndrome)/AML has been reported in up to 10% of patients at 10 years post transplant.…”
Section: Discussionmentioning
confidence: 99%